PENGUJIAN MARKET EFFICIENCY: PEMBUKTIAN FENOMENA ANOMALI PASAR PADA STRAIT TIMES INDEX DI BURSA EFEK SINGAPURA - Christian Adrianus Harijanto; Sri Lestari Kurniawati (Journal of Business & Banking, 2013)
Market efficiency has become a vital discussion so far. Therefore, it is a good effort when the study attempts to analyze factors in market efficiency. This study tries to investigate the existence of the market anomalies such as Monday Effect, Week-four Effect, and January Effectin Singapore Stock Exchange during the period of 1 January 2010 to 31 December 2012.Using non-random sampling technique, especially the purposive sampling, this study took 27 companies from the Strait Times Index as the sample of this study. The data used in this research comes from the daily closing prices of the samples. The three hypotheses are tested by means of independent sample t-test. The result shows that there is no evidence of the market anomalies phenomenon on Strait Times Index. Neither of Monday Effect, Weekfour Effect, and January Effect exist in Singapore Stock Exchange during the period of this study. The disappearance of this phenomenon is suspected as a result of the global economic crisis which led to changing the investors trading behavior in capital market. Furthermore, the characteristic of the Singaporean investor and the Governments policy about tax regulation are also another reason why this phenomenon doesnt exist in Strait Times Index.